Investing in Communities Achieves Results : Findings from an Evaluation of Community Responses to HIV and AIDS - Rodriguez-García, Rosalía; Bonnel, René; Wilson, David; N'Jie, N'Della (Washington, DC: World Bank, 2013)
The overview summarizes the evaluation of community responses (15 studies, including 11 evaluations carried out in 8 countries). It presents the evaluation questions, the methodology, the key results achieved by community responses along the continuum of prevention, treatment, care and support, and the resulting policy and programmatic implications. Before the scale-up of the international response to the AIDS pandemic, community responses in developing countries played a crucial role in providing services and care for those affected. This study is the first comprehensive, mixed-method evaluation of the impact of that response. The evaluation finds that community response can be effective at increasing knowledge of HIV, promoting social empowerment, increasing access to and use of HIV services, and even decreasing HIV incidence, all through the effective mobilization of limited resources. By effectively engaging with this powerful community structure, future HIV and AIDS programs can ensure that communities continue to contribute to the global response to HIV and AIDS.